Synthesis, characterization and biological activity of new mixed-ligand divalent metal complexes derived from 1,3,4-thiadiazole Schiff base and 2,2′‐bipyridine (Sulaimani Journal for Pure and Applied Sciences, 2021)
New mixed-ligand complexes of Cu(II), Ni(II), Co(II), Zn(II), Pt(II) and Pd(II) transition metals were synthesized from a Schiff base 5-((Z)-((E)-3-phenylallylidene)amino)-1,3,4-thiadiazole-2-thiol obtained by the condensation reaction between cinnamaldehyde and 5-amino-1, 3, 4-thiadiazol-2-thiol as a primary ligand (LH1) and the heterocyclic base 2,2′‐bipyridine (2,2′-bipy) as a secondary ligand (L2). The prepared ligand and their metal complexes have been characterized by elemental analysis, molar conductivity measurement, magnetic susceptibility, infrared (FT-IR), proton nuclear magnetic resonance (1H-NMR), electronic (UV-Vis), mass spectrometry (MS), thermal gravimetric analysis (TGA), and screened in vitro for their potential as biological activity by the agar well diffusion method against Gram-negative Escherichia coli (E. coli) and Gram-Positive Staphylococcus aureus (S. aureus) strain. The mixed-ligand complexes were found to have the following formulas [M (L1)(L2)]Y ⋅H2O L1 = Schiff base, L2 = 2,2′-bipy, (M = Cu(II), Ni(II), Co(II), Zn(II), Y=NO3), (M=pd(II), Y=Cl2) and (M= pt(II), Y=Cl) for metallic complexes. L1 acts as a bidentate ligand and coordinates to a metallic ion center through imine nitrogen and a deprotonated sulfur atom. Similarly, L2 acts as a neutral bidentate ligand coordinating to the metallic ions via two nitrogen atoms. The resultant data have shown that the mixed-ligand complexes have an electrolytic nature and Co(II), Pt(II), and Pd(II) metal complexes have square planer structure, as well as tetrahedral geometry, has been proposed for the complexes of Cu(II), Ni(II) and Zn(II). Thus, the biological activity data indicated that the Cu(II), Co(II), Zn(II), and Pd(II) complexes have a much higher biological activity than the Schiff base. It was found that the Zn(II) complex was more effective than the other metal complexes used against both types of the bacteria tested.
Keywords: Mixed- ligand complexes; Schiff base ligand; 2,2′‐bipyridine; transition metals; antibacterial activity